Arthroscopic treatment of meniscal tears: with all-inside suture technique: 1 years follow up results - Di Benedetto, P.; Beltrame, Al.; Beltrame, Ar.; Gisonni, R.; Cainero, V.; Causero, A. (Acta Biomedica Atenei Parmensis, 2014)
Background: In the last years meniscal repair surgeries have evolved to less invasive all-arthroscopic technique. Purpose: To determine the short-term success rate and reoperation rate of all-inside meniscal sutures with a concomitant anterior cruciate ligament reconstruction. Methods: Eighteen meniscal repairs were performed using an all inside suture technique. A concomitant anterior cruciate ligament reconstruction was done in all patients.The mean follow-up was 14 months (range 12-18). The success rate was determined by the presence of normal or nearly normal parameters of the Henning Classification based on magnetic resonance imaging. Results: Sixteen (89%) of the meniscal repairs had normal or nearly normal characteristics according to Henning Classification. Two patients (11%) required partial arthroscopicmeniscectomy. Conclusions: Current techniques do not require accessory posteromedial or posterolateral incisions and significantly reduce the incidence of complications and pain associated with more invasive surgery. The short-term evaluation of the meniscal repairs with concomitant anterior cruciate ligament-reconstruction shown good results with satisfaction of the patients. (www.actabiomedica.it)